Acute Hematogenous Periprosthetic Hip Infection by Gemella morbillorum, Successfully Treated with Debridement, Antibiotics and Implant Retention: A Case Report and Literature Review of Osteoarticular Gemella morbillorum Infections - Albert Pardo-Pol; Daniel Pérez-Prieto; Albert Alier; Lucas Ilzarbe; Lluïsa Sorlí; Lluis Puig; Santos Martínez-Díaz; Joan Gómez-Junyent (Tropical Medicine and Infectious Disease, 2022)
Gemella morbillorum is a facultative anaerobic, catalase-negative and non-spore forming Gram-positive cocci. It can be found as part of the normal oropharyngeal flora, in the gastrointestinal tract and the female genital tract. However, it can be a causal agent of infections such as endocarditis, meningitis or brain abscesses, and very rarely can cause osteoarticular infections. Herein, a case report of an acute hematogenous prosthetic hip infection caused by Gemella morbillorum, successfully treated with a DAIR and beta-lactam antibiotic therapy, is presented. We provide a literature review of the other orthopedic-related infections caused by this microorganism.